Molecular docking and dynamics simulations on the interaction of cationic porphyrin–anthraquinone hybrids with DNA G-quadruplexes. Issue 2 (1st February 2016) - Arba, Muhammad; Kartasasmita, Rahmana E.; Tjahjono, Daryono H.
Abstract : A series of cationic porphyrin–anthraquinone hybrids bearing either pyridine, imidazole, or pyrazole rings at the meso -positions have been investigated for their interaction with DNA G-quadruplexes by employing molecular docking and molecular dynamics simulations. Three types of DNA G-quadruplexes were utilized, which comprise parallel, antiparallel, and mixed hybrid topologies. The porphyrin hybrids have a preference to bind with parallel and mixed hybrid structures compared to the antiparallel structure. This preference arises from the end stacking of porphyrin moiety following G-stem and loop binding of anthraquinone tail, which is not found in the antiparallel due to the presence of diagonal and lateral loops that crowd the G-quartet. The binding to the antiparallel, instead, occurred with poorer affinity through both the loop and wide groove. All sites of porphyrin binding were confirmed by 6 ns molecular dynamics simulation, as well as by the negative value of the total binding free energies that were calculated using the MMPBSA method. Free energy analysis shows that the favorable contribution came from the electrostatic term, which supposedly originated from the interaction of either cationic pyridinium, pyrazole, or imidazole groups and the anionic phosphate backbone, and also from the van der Waals energy, which primarily contributed through end stacking interaction.